Formula Analysis of Tembang Batanghari Sembilan Arts: A Lacanian Perspective - Lussy Albayinnah (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Oral tradition is considered as one of some enriched Indonesian cultures that have been preserved from former generation to the following ones. It also provides a great deal of opportunity to be studied in the scope of literary studies with various approaches. One oral tradition that owns these characteristics is the Batanghari Sembilan art songs that originated from the South Sumatra region. This study aims to find out the similarities and differences between two Batanghari Sembilan art songs entitled Iluk Pule and Umak di Doson, Bapak Jao, which can be seen from the formula and formulaic structures as well as the indications of desire found in the composition of the text through Lacan's psychoanalytic perspective. Qualitative research methods and content analysis were carried out to analyze the data in the form of the structure of the formula and the concept of desire found in the sentences of the Batanghari Sembilan oral text. The results of the study highlight the similarities of the types of formulas found in the two songs, namely the presence of morphological formulas, alliterations, tautotes and phonemic formulas, and the absence of anaphora and anadiplosis formulas in Umak in Doson, Bapak Jao. Some repetitive words are acknowledged as an attempt to emphasize the meaning and promote the songs’ originality. In addition, the two songs have different desires, namely the desire to have a lover and the desire to live together with parents. The similarity found in the two songs is the positioning of the mother's wishes as a substitute for one's own desires which are conveyed by the individual metonymically.